Maintaining Sustainable Collaboration in Building Disclosure at Local Public Bodies between Public Information Commission of West Kalimantan and Civil Society Organizations (Forum Ilmu Sosial, 2020)
The resistance of public institutions to share and disseminate public information, and the limited authority of the Public Information Commission of West Kalimantan, may cause the lack of transparency of public institution. To overcome it, innovative efforts and active involvement of many stakeholders including civil society organizations are needed. In 2017-2018, many innovative products to overcome the lack of transparency of public institutions were produced by Public Information Commission of West Kalimantan and local civil society organizations. In the same year, the local government was awarded as the most transparent provincial government. The main question is how the collaboration between the Public Information Commission of West Kalimantan and local civil society organizations can be maintained to be sustainable, because each actor has the same purposes. The research purposes are to identify the needs for collaboration and the opportunity for sustainable collaboration. The results showed that the opportunity is possible with some requirements to build and maintain sustainable collaboration.